1980
DOI: 10.1093/ajcn/33.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mediated immunity in genetically obese (C57BL/6J ob/ob) mice

Abstract: The thymus and spleen of genetically obese (C57BL/6J ob/ob) mice weighed less and contained fewer mononuclear cells and Thy 1.2-positive lymphocytes compared with findings in lean controls. The number of splenic antibody forming cells, particularly IgG-producing lymphocytes, was reduced. There was a marked increase in natural killer cell activity and a slight increase in antibody-dependent cell-mediated cytotoxicity in the obese animals. Cytotoxic response of spleen cells of obese mice immunized in vivo was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
1
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(100 citation statements)
references
References 0 publications
2
91
1
6
Order By: Relevance
“…In addition, human white blood cell counts are correlated with body mass index and serum leptin levels [23]. Moreover, diminished cell-mediated immunity and decreased lymphocyte counts have been reported in ob/ob and db/db mice [24,25].We demonstrate here that leptin receptor messenger RNA is expressed in lymphoid tissue, and that leptin both restores the decrease in lymphocyte numbers normally observed in fasted mice and prevents apoptosis of lymphocytes in steroidinjected mice. Consistent with the observed anti-apoptotic effect of leptin, we observed up-regulation of the bcl-xL gene by leptin.…”
supporting
confidence: 56%
“…In addition, human white blood cell counts are correlated with body mass index and serum leptin levels [23]. Moreover, diminished cell-mediated immunity and decreased lymphocyte counts have been reported in ob/ob and db/db mice [24,25].We demonstrate here that leptin receptor messenger RNA is expressed in lymphoid tissue, and that leptin both restores the decrease in lymphocyte numbers normally observed in fasted mice and prevents apoptosis of lymphocytes in steroidinjected mice. Consistent with the observed anti-apoptotic effect of leptin, we observed up-regulation of the bcl-xL gene by leptin.…”
supporting
confidence: 56%
“…Leptin-deficient rodents used as models for insulin resistance are hyperinsulinemic, insulin-resistant, and immuno-compromised (Meade et al 1979, Chandra 1980, Zhang et al 1994, Lord et al 1998, Howard et al 1999. Importantly, these observations are, in part, opposite to the human scenario where obese individuals that develop insulin resistance exhibit high leptin levels and an induction of inflammation (Gregor & Hotamisligil 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of leptin have also been investigated in patients with Rett syndrome (n=16), where it was found that leptin was significantly increased compared to healthy controls (n=16), but also did not correlate with obesity (Blardi et al, 2008), suggesting that there may be more to the actions of leptin in neurodevelopment than weight balance. The immunomodulatory properties of leptin were first reported on a mouse model, in which obese mice were found to have impaired cell-mediated and humoral immunity, attributed to possible lack of leptin (Chandra, 1980). The epigenetic status in adulthood was shown to be directionally dependent on prenatal nutritional status (Gluckman et al, 2007) and neonatal leptin administration late in the phase of developmental plasticity was able to reverse the developmental programming in rats (Vickers et al, 2005).…”
Section: Other Perinatal Risk Factorsmentioning
confidence: 99%